Research on the inheritance and protection of intangible cultural heritage under the perspective of metauniverse - Wu, Jian (Transactions on Economics, Business and Management Research, 2024)
Nowadays, with the rapid development of Chinese society in various fields, in this environment, new things continue to produce, leading to many traditional things have been withdrawn from the stage.